Religious centrality across 22 countries - Robert D. Woodberry; Kathryn A. Johnson; Brendan Case; Matt Bradshaw; Tyler J. VanderWeele; Byron R. Johnson (Scientific Reports)
Abstract Religious Centrality has been widely studied in Europe and North America and is generally associated with better psychological and social outcomes. Religious centrality is often assessed as a measure of intrinsic religiosity (IR)—religion as one’s guiding approach to life – and has been widely validated in societies around the world. However, most studies of religious centrality/IR are cross-sectional and use samples from ‘Western’ societies or samples from single non-European societies. Moreover, most samples are not nationally representative. Systematic comparisons are difficult because the samples, measures, and procedures vary between studies. This article examines religious centrality across 22 nationally representative samples from religiously diverse countries from the 1st wave of the Global Flourishing Study (GFS) using a single-item IR measure and identical demographic measures and methods in each country. The study will serve as the foundation for longitudinal studies designed to assess the causal impact of religious centrality on human flourishing. In the current study, we find societies range widely, with religious centrality lowest in Europe and East Asia, moderate in the Americas and Israel, and highest in Africa and the rest of Asia. We discuss the complexities of assessing religious centrality across religious traditions, how the demographic factors associated with religious centrality vary between countries, and provide implications for secularization theory as well as theories of human flourishing.